Trigeminal Schwannoma: A Retrospective Analysis of Endoscopic Endonasal Management, Treatment Outcomes, and Neuropathic Sequelae - Patel, Vijay A.; Polster, Sean P.; Abou-Al-Shaar, Hussam; Kalmar, Christopher L.; Zenonos, Georgios A.; Wang, Eric W.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Introduction Trigeminal schwannomas (TS) are rare skull base tumors that have been associated with significant neuropathic sequalae for patients. The authors aim to evaluate the clinical features, treatment outcomes, and neuropathic sequelae following endoscopic endonasal approach (EEA) for TS.Methods The study involves a retrospective review of patients who underwent EEA for resection of TS at a single academic institution between 2004 and 2020. Radiographic and clinical data were recorded and analyzed.Results A total of 16 patients were abstracted, with a mean age at the time of surgery of 44 years with a slight female (1.83:1) predominance. Primary preoperative symptomatology included facial pain/neuralgia (n = 5, 31.3%), facial hypoesthesia (n = 4, 25.0%), and headache (n = 4, 25.0%). Following TS resection, patients were found to have facial hypoesthesia (n = 11, 68.8%), neuropathic keratopathy (n = 4, 25.0%), and mastication musculature atrophy (n = 3, 18.8%). Patients with preoperative facial pain/neuralgia (n = 5, 31.3%) were significantly more likely to try adjunctive pain therapies (p = 0.018) as well as seek pain consultation (p = 0.018). Patients with preoperative migraines (n = 2, 12.5%) were significantly more likely to trial adjunctive pain therapies (p = 0.025) and undergo evaluation with pain specialists (p = 0.025). Finally, patients with preoperative pharmacologic agent utilization were significantly more likely to trial adjunctive pain therapies (p = 0.036) and pursue pain consultation (p = 0.036).Conclusion Some degree of trigeminal dysfunction may be more common than previously reported following EEA for TS resection. Factors that appear to play a role in the development of trigeminal dysfunction include pre-existing pain syndromes such as facial pain/neuralgia or headache and preoperative medication utilization.
Keywords: endoscopic endonasal approach; trigeminal neuropathy; outcomes; trigeminal nerve; trigeminal schwannoma